Roman Road Station Gensis - Popović, Goran D. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
Gensis was the first road station on the Roman road Sirmium – Argentaria, which connects the capital of the province of Pannonia Inferior with rich silver mines along the middle course of the Drina River. According to Tabula Peutingeriana, the distance between Sirmium and Gensis was 30 Roman miles, or about 42 km, while distance Gensis – Ad Drinum was 15 Roman miles or about 22 km. A. Boué has located Gensis in the territory of modern town Loznica. However, in the territory of the town of Loznica, as well as suburban settlements, no archaeological findings have been discovered so far that would be related to the ancient period. Starting from the assumption that Gensis was the administrative vicus of the ancient mines in the lower course of the Drina River, S. Dušanić proposed that its location was in the village of Rumska, on the eastern slopes of Mount Cer. However, the position of the Rumska village in relation to Roman communication in the Drina valley leads to the conclusion that the mentioned village cannot be the location of Gensis. According to F. Kanitz, Gensis road station was located on top of the Vidojevića hill. The existence of archaeological remains at the top of Vidojevića hill indicates that a Roman settlement could be found on its slopes. In support of locating the Gensis road station on Vidojevića, the data from the Tabula Peutingeriana supports this. However, although more field reconnaissance has been carried out so far in the vicinity of Vidojevića, it is noticeable that there are no archaeological sites from the ancient period in the villages on the right side of the Drina River, nor any epigraphic and numismatic findings. In contrast, the archaeological finds of building materials, necropolises, and coins dating from the Roman period indicate that the Roman settlement was located on the left bank of the Drina River, near the town of Janja. The information we currently have is not sufficient to determine the location of the Gensis road station with certainty. However, two sites stand out as potential locations: Vidojevića Hill, east of Lešnica and Pačići, west of Janja.
Keywords: Argentaria; Sirmium; Pannonia Inferior; Roman roads; road station; Gensis